2017
DOI: 10.1038/s41598-017-08447-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hypoxic response decreases stemness and reduces tumorigenic signaling due to impaired assembly of HIF1 transcription complex in pancreatic cancer

Abstract: Pancreatic tumors are renowned for their extremely hypoxic centers, resulting in upregulation of a number of hypoxia mediated signaling pathways including cell proliferation, metabolism and cell survival. Previous studies from our laboratory have shown that Minnelide, a water-soluble pro-drug of triptolide (anti-cancer compound), decreases viability of cancer cells in vitro as well as in vivo. However, its mechanism of action remain elusive. In the current study we evaluated the effect of Minnelide, on hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 35 publications
4
42
0
Order By: Relevance
“…While they are probably not a population that is responsible for the origin of pancreatic tumors, our previously published study definitely show that they are responsible for therapeutic resistance, tumor initiation at very low dilution as well as extreme metastasis 2, 24, 26 . Our studies further show that this population is enriched upon nutritional deprivation, low dose chemotherapy as well as presence of hypoxia 21, 25, 26 . We and others have shown that CD133+ population are generally slow-cycling or quiescent 2, 6, 36 .…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…While they are probably not a population that is responsible for the origin of pancreatic tumors, our previously published study definitely show that they are responsible for therapeutic resistance, tumor initiation at very low dilution as well as extreme metastasis 2, 24, 26 . Our studies further show that this population is enriched upon nutritional deprivation, low dose chemotherapy as well as presence of hypoxia 21, 25, 26 . We and others have shown that CD133+ population are generally slow-cycling or quiescent 2, 6, 36 .…”
Section: Introductionsupporting
confidence: 70%
“…Similar observation was made in other pancreatic cancer cell line as well (Supplementary Figure 3A, B). Previously published results from our laboratory show that under all these conditions, CD133 expression was upregulated as well 21, 25 . Our previously published work has shown that chemotherapy selected for treatment refractory CD133+ population 25 .…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations